Colistin Therapy-induced Acute Kidney Injury: A Case Report - Ujwala, Veeram Reddy; Suchitra, Uppicherla; Farheen, Shaik Hazira; Iram, Shaik Rahila; Priya, Govindarajulu (Indian Journal of Pharmacy Practice)
Nephrotoxicity refers to the RIFLE (R-risk, I-injury, F-failure, L-loss of function, E-end stage renal failure) categories. It is genetically acquired, caused by drugs, and also related secondarily to diabetes, liver problems, and cardiac problems. Drug-induced nephrotoxicity is dose-dependent. Colistin drug usage is uttermost in usage due to Multi-Drug Resistant (MDR) infections caused by gram-negative bacteria like Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii. We are reporting a case of a 62-year-old male patient suffered from Venous thromboembolism and Anemia who underwent fasciotomy later suffered with Hospital Acquired Pneumonia (HAP) caused by MDR Acinetobacter baumannii sensitive to only colistin and meropenem. Two days after the initiation of therapy, urine output was decreased (Oliguria-<500 mL), creatinine levels were increased to 3.08mg/dL and renal parenchymal changes were observed in USG. His laboratory reports suggest he developed Acute Kidney Injury (AKI) Colistin shows a probable (Naranjo score-8) causal relationship with AKI. The dose of the drug was not altered or stopped. Creatinine and BUN levels were closely monitored. After 14 days, urine output was increased to 2400mL. Other neurological side effects of Colistin such as respiratory failure was not observed. On the day of discharge, the patient was stable and improved. This means that if the benefit outweighs the risk, there is no need to discontinue the drug; close monitoring will reduce side effects.
Keywords: Acinetobacter boumannii; Oliguria; MDR; Nephrotoxicity; RIFL